Antioxidant phenolic and quinonemethide triterpenes from Cheiloclinium cognatum - Jeller, A. H.; Silva, DHS; Liao, L. M.; Bolzani, Vanderlan da Silva [UNESP]; Furlan, Maysa [UNESP] (Elsevier B.V., 2004)
The triterpenes, 22beta-hydroxypristimerin and cognatine, were isolated together with the known compounds pristimerin, maytenin, 20alpha-hydroxymaytenin, 22beta-hydroxymaytenin, netzahualcoyol, netzahualcoyondiol and netzahualcoyone from root bark of Chei-Ioclinium cognatum. The structures of the isolated compounds were elucidated by interpretation of their spectral data, including gHMQC and gHMBC experiments. The isolates were investigated for their radical scavenging abilities through a spectrophotometric assay involving reduction of 2,2-diphenyl-picryl hydrazyl (DPPH). (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Cheiloclinium cognatum; hippocrateaceae; quinonemethide triterpenes; phenolic triterpene; antioxidant activity